PENGARUH KOMPETENSI, INDEPENDENSI DAN ETIKA PROFESI AUDITOR TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KAP DI MALANG) - Maharany Maharany; Yuli Widi Astuti; Dodik Juliardi (Universitas Negeri Malang, 2016)
This study aims to analyze the effect of competence, independence, and auditor’s professional ethic toward audit quality in public accountant firm located in Malang. The finding of this research suggested that competence and independence did not significantly influence the audit quality, while the auditor’s professional ethic had a significant influence on it.Keywords: competence, independence,auditor’s professional ethic, audit quality